Characterization of high- and low-molecular-weight glutenin subunits from Chinese Xinjiang wheat landraces and historical varieties - Dai, Shoufen (J Food Sci Technol, 2020)
Landraces and historical varieties are necessary germplasms for genetic improvement of modern cereals. Allelic variations at the Glu-1 and Glu-3 loci in 300 common wheat landraces and 43 historical varieties from Xinjiang, China, were evaluated by Sodium-dodecyl-sulfate polyacrylamide gel electrophoresis (SDS-PAGE) and allele-specific molecular markers. Among the materials investigated, three, nine, and seven alleles were identified from the Glu-A1, Glu-B1, and Glu-D1 loci, respectively, and a total of 26 high-molecular-weight glutenin subunit (HMW-GS) combinations were found, of which 18 combinations were identified in landraces and historical varieties. Allelic frequency of HMW-GS combinations null, 7 + 8, 2 + 12 was found to be the highest in both the landraces (63.3%) and historical varieties (39.5%). Besides, some distinctive HMW-GS alleles, such as the novel Glu-B1 allele 6.1* + 8.1* and Glu-D1 alleles 2.6 + 12, 2.1 + 10.1, and 5** + 10 were observed in Xinjiang wheat landraces. Among the Glu-A3 and Glu-B3 loci of landraces and historical varieties, a total of eight and nine alleles were found, respectively. At each locus, two novel alleles were identified. A total of 33 low-molecular-weight glutenin subunit (LMW-GS) combinations of Glu-A3 and Glu-B3 were identified, with 31 and 14 combinations occurring in landraces and historical varieties, respectively, but only 10 combinations shared by both of them. As Glu-D1, Glu-A3, and Glu-B3 have highest contribution to the end-use quality and processing properties as compared to Glu-A1, Glu-B1, and Glu-D3 locus, the novel or distinctive HMW-GS and LMW-GS alleles in these loci could potentially be utilized for the improvement in the quality of modern wheat. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13197-020-04414-5) contains supplementary material, which is available to authorized users.